Neurotheology of Islam and Higher Consciousness States - Bragazzi, Nicola Luigi; Khabbache, Hicham; Vecchio, Ignazio; Martini, Mariano; Zerbetto, Riccardo; Re, Tania Simona (Cosmos and History: The Journal of Natural and Social Philosophy, 2018)
Generally speaking, human life is characterized by an array of experiences, which, both in health and disease, can have a spiritual/religious dimension. In the last decades, spirituality/religiosity has attracted a huge body of research and neurotheology or spiritual neuroscience is emerging as a modern multidisciplinary field aimed at understanding religious experiences and practices, as well its impact on well-being, with a focus on mental health, and its potential therapeutic implications in the treatment of neuropsychiatric disorders. For this purpose, neurotheology combines a variety of approaches and theoretical frameworks, deriving influences from theology, divinities and religious studies, philosophy, sociology, cognitive science, neuroscience, psychology, and anthropology. Available scientific evidences seem to suggest that Islam and Sufism (prayer and meditation) can contribute to the achievement of higher consciousness states.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false IT X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->